Rutin, a Quercetin Glycoside, Restores Chemosensitivity in Human Breast Cancer Cells. (28th July 2017) - Iriti, Marcello; Kubina, Robert; Cochis, Andrea; Sorrentino, Rita; Varoni, Elena M.; Kabała‐Dzik, Agata; Azzimonti, Barbara; Dziedzic, Arkadiusz; Rimondini, Lia; Wojtyczka, Robert D.
Abstract : Several studies have documented the ability of flavonoids to sensitize cancer cells to chemotherapeutics and reverse multidrug resistance by inhibition of efflux pumps (adenosine triphosphate‐binding cassette transporters), apoptosis activation, and cell cycle arrest. In this study, the flavonoid rutin (quercetin 3‐ O ‐β‐d ‐rutinoside) was investigated as chemosensitizer towards two different human epithelial breast cancer cell lines: (i) MB‐MDA‐231, selected as representative for triple‐negative breast cancer and (ii) MCF‐7 used as a well‐characterized model of HER2‐negative breast cancer. To assess the cytocompatibility of rutin against non‐cancer cells, primary human mammary fibroblasts were used as control and non‐target cells. In MDA‐MB‐231 cells, 20 μM rutin enhanced cytotoxicity related to cyclophosphamide and methotrexate. Rutin significantly ( p  < 0.05) increased the anticancer activity of both chemotherapeutics, at 24–48–72 h, and decreased the activity of the adenosine triphosphate‐binding cassette transporters, namely, P‐glycoprotein (P‐gp) and breast cancer resistance protein (BCRP). Flow cytometry analysis showed 20 μM and 50 μM rutin arrested cell cycle at G2/M and G0/G1 phases, respectively, significantly promoting cell apoptosis. Rutin, via non‐selective inhibition of P‐gp and BCRP pumps, efficiently reverses multidrug resistance and restores chemosensitivity to cyclophosphamide and cyclophosphamide of human chemoresistant, triple‐negative breast cancer cells, successfully arresting cell cycle progression. Copyright © 2017 John Wiley & Sons, Ltd.